Surface runoff in varying forest cover types in Jangkok Watershed, Lombok Island, Indonesia - MARKUM MARKUM; FIRMAN ALI RAHMAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Markum, Rahman FA. 2024. Surface runoff in varying forest cover types in Jangkok Watershed, Lombok Island, Indonesia. Biodiversitas 25: 753-761. Forests in the Jangkok Watershed play an important role in controlling ecological functions and hydrological cycles in Lombok Island, West Nusa Tenggara, Indonesia. This research aims to evaluate the amount of surface runoff in the Jangkok Watershed by looking at various types of forest cover, namely Primary Forest (PF), Disturbed Forest (DF), Candlenut Agroforestry (CA), Mahogany Woodlot (MW), Multistrata Agroforestry (MA) and Simple Agroforestry (SA). The research area was located at altitudes between 250-650 meters above sea level with a slope of 7-43%. Data collected on each type of forest cover included: vegetation characteristics, surface runoff, slope and rainfall. The result shows vegetation cover in the studied area varies from moderate to very dense with coverage ranging from 50-90%. The vegetation in PF, DF and MA are characterized by very diverse vegetation, while that in UM, CA and SA it is quite homogeneous. The amount of Surface runoff coefficient varies across forest cover types with PF being the lowest (0.6-1.4%), followed by DF (0.6-1.7%), MA (0.6-1.7%), MW (0.6-2.1%), SA (1.0-2.2%) and CA (1.8-4.3%). Factors that are considered influential in determining the magnitude of surface runoff at the research location are the physical properties of the soil, rainfall intensity, vegetation type, structure and density, and land slope. The findings of this study suggest that more complex vegetation has important role in minimizing surface runoff, highlighting the importance of preserving and protecting this forest type to maintain hydrological function of watershed.